2020
DOI: 10.1073/pnas.2001933117
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induces dynamic changes to the T cell repertoire in renal cell carcinoma patients

Abstract: Clinical studies combining radiation and immunotherapy have shown promising response rates, strengthening efforts to sensitize tumors to immune-mediated attack. Thus, there is an ongoing surge in trials using preconditioning regimens with immunotherapy. Yet, due to the scarcity of resected tumors treated in situ with radiotherapy, there has been little investigation of radiation’s sole contributions to local and systemic antitumor immunity in patients. Without this access, translational studies have been limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 59 publications
4
52
0
Order By: Relevance
“…This suggests that the clonal expansion of TIL could be induced by the stimulation of neoantigens derived from tumor cells through the process consisting of cancer antigen presentation, the priming and trafficking of T cells, and infiltration of T cells into tumors, which is commonly known as “the cancer-immunity cycle” reviewed by Chen and Mellman [ 30 ]. We also investigated whether the oligoclonality of TIL was more significantly induced after definitive CRT, because radiation and chemotherapy have been previously reported to induce neoantigens by disrupting cancer cells [ 17 , 31 , 32 ]. Preferably, we could compare the clonality of TIL between stage-adjusted ESCCs with and without preceding definitive CRT directly; however, it is difficult to recruit patients with stage II or III ESCCs that did not have preceding neoadjuvant therapies in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the clonal expansion of TIL could be induced by the stimulation of neoantigens derived from tumor cells through the process consisting of cancer antigen presentation, the priming and trafficking of T cells, and infiltration of T cells into tumors, which is commonly known as “the cancer-immunity cycle” reviewed by Chen and Mellman [ 30 ]. We also investigated whether the oligoclonality of TIL was more significantly induced after definitive CRT, because radiation and chemotherapy have been previously reported to induce neoantigens by disrupting cancer cells [ 17 , 31 , 32 ]. Preferably, we could compare the clonality of TIL between stage-adjusted ESCCs with and without preceding definitive CRT directly; however, it is difficult to recruit patients with stage II or III ESCCs that did not have preceding neoadjuvant therapies in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in molecular biology and tumor immunology have revealed the fact that the therapeutic effects of chemotherapy or radiation should be greatly influenced by the tumor immunologic microenvironment [ 14 , 15 , 16 , 17 ]. Actually, many studies have suggested that the factors relating to the tumor microenvironment (TME), such as PD-L1 expression or the presence of tumor-infiltrating lymphocytes (TIL), could be prognostic or predictive marker candidates for chemotherapy or chemoradiation in various types of human cancers, including ESCC [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other major immunogenic features of RT is to shape the T cell receptor (TCR) repertoire of TILs (108)(109)(110)(111)(112) and to expose immunogenic mutations to the immune system (113). A detailed discussion describing the mechanisms responsible for the increase of antigenicity in irradiated tumors can be found elsewhere (114).…”
Section: Radiotherapy To Restore the Sensitivity Of Glioblastoma To Immunotherapymentioning
confidence: 99%
“…Emerging combinations also include ICIs associated with radiotherapy [136]. Radiotherapy remodels intratumoral T cell responses and supports refined sequencing of combination strategies in RCC [183]. The specific observations of T cell expansion and contraction within distinct time points of observation offer a rationale for the timing of combination strategies that leverage endogenous T cell responses to improve patient outcomes [183].…”
Section: Combination Strategies: Ici + Radiotherapymentioning
confidence: 99%
“…Radiotherapy remodels intratumoral T cell responses and supports refined sequencing of combination strategies in RCC [183]. The specific observations of T cell expansion and contraction within distinct time points of observation offer a rationale for the timing of combination strategies that leverage endogenous T cell responses to improve patient outcomes [183]. RCC patients treated with SBRT exhibit broad transcriptional immune activation and increased clonality, with an underlying heightened proportion of dominant motifs [183].…”
Section: Combination Strategies: Ici + Radiotherapymentioning
confidence: 99%